Tellurium analyses of 12 samples of manganese oxide nodules from the Pacific and Indian Oceans - H W Lakin; C E Thompson; D F Davidson (PANGAEA, 2023)
As a part of a continuing study of the distribution and abundance of tellurium in various materials of the earth extquotesingles crust, analyses were made of 12 samples of manganese nodules from the Pacific and Indian Ocean. The quantitative determination of tellurium is based on the induced precipitation of elemental gold from a 6NHCl solution containing gold chloride, cupric chloride, and hypophosphorous acid; the amount of gold reduced is proportional to the amount of tellurium present. As little as 1 nanogram (1 exttimes 10-9 g) of tellurium gives a measurable reaction with 1 mg of gold in 50 ml of solution.